(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
The effect of high temperature on some physiological traits of wheat has been studied under controlled condition in a green house. The temperature stress chosen for the study were 25±1/14±10C (control) 28±1/18±10C day/night and 35±1/25±10C day/night temperature. Total crop duration was reduced under higher temperature. The results showed that leaf dry weight, shoot dry weight, flag leaf area of wheat was reduced under higher temperature. High temperature brought sterility and consequently reduced grain yield. Wheat plant grown under 35±1/25±10C, day night temperature failed to form any seed. Chlorophyll content also directly related to grain weight. High temperature reduced leaf chlorophyll content as well as grain weight. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21332 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 103-110, 2014